The Influence of Profitability, Liquidity, Leverage and Company Size on Stock Returns - M. Alvinnur Azizi; Umaimah Umaimah; Nyimas Wardatul Afiqoh (Indonesian Vocational Research Journal, 2023)
The purpose of this study is to determine the effect of profitability, liquidity, leverage and size of the company to stock return on manufacturing companies in Indonesian Stock Exchange (Idx). In this study the independent variables used are profitability measured by using Return On Assets (ROA), liquidity measured by using Current Ratio, leverage is measured by using Debt to Equity Ratio (DER) and firm size measured by using Ln (Size). Stock Return in this research is used as dependent variable. This study was conducted on manufactured companies listed on manufacturing companies in Indonesian Stock Exchange (Idx) 2017-2019. Using purposive sampling technique, resulting 71 companies as a research sample. Data analysis techniques used are multiple linear regression analysis. Based on the results of the research shows that profitability, liquidity and leverage do not has a significant effect on stock return, while firm size have a significant effect on stock return.